(untitled) (Saptagandaki Journal, 2024)
This study has been designed to extract the factors affecting corporate governance in the Nepalese telecommunication sector. The study aims to explore the impact of ownership structure, board leadership, board diversity, political influence, globalization, and technology on corporate governance. Employing a descriptive and explanatory research design, the study adopts a quantitative approach, utilizing a descriptive research design to gather data from 155 respondents. The study also utilizes a stratified-sampling technique to select its sample. Correlation and regression analyses were conducted to evaluate the relationship between independent and dependent variables. This research investigates the factors influencing corporate governance in the Nepalese telecommunication sector, potentially supporting the implementation of effective corporate governance practices within Nepal’s Telecommunication industry. The study reveals significant relationships between ownership structure, board leadership, board diversity, political influence, globalization, technology, and corporate governance. Notably, ownership structure has a negative impact on corporate governance. This analysis contributes to improving firm performance by analyzing the factors affecting corporate governance and sheds light on the relative impact of those factors on corporate governance in the Nepalese telecommunication sector.